Reciprocal constructions - Загнітко, А.; Путіліна, О. (Мовознавство, 2013)
Рецензія на книгу: Reciprocal constructions / Ed. by V. P. Nedjalkov; With the assistance of E. S. GeniuSiene and Z. Guentcheva; Foreword by B. Comrie
Amsterdam; Philadelphia : John Benjamins Publishing Company, 2007.— xxiii, 2219 pp.— 5 vols. (Typological Studies in Language (TSL), 71).